Effect of different annealing environments on the solar cell performance of CdSe pebbles. (15th April 2016) - Pawar, Sachin A.; Patil, Dipali S.; Suryawanshi, Mahesh P.; Ghorpade, Uma V.; Lokhande, Abhishek C.; Park, Ju Young; Chalapathy, R.B.V.; Shin, Jae Cheol; Patil, Pramod S.; Kim, Jin Hyeok
Abstract: Cadmium selenide pebbles have been synthesized by a simple and cost-effective chemical bath deposition method. In order to study the effect of different annealing environments, the CdSe thin films were annealed in air, nitrogen, argon and in a vacuum at 300 °C for 1 h. The optical, structural, compositional, and morphological properties of the films were then analyzed using UV–vis spectrophotometry, photoluminescence, X-ray diffraction, X-ray photoelectron spectroscopy, and field emission scanning electron microscopy. XRD patterns revealed the formation of amorphous CdSe thin films. Annealing entails a change in crystal structure, from amorphous to hexagonal. The chemical composition and valence states of the constituent elements were analyzed by XPS. FESEM images showed the formation of CdSe pebbles in all the samples with voids between the pebbles, but the samples annealed in a vacuum had fewer voids than did other samples. Under AM 1.5G illumination, the photoanodes had an improved power conversion efficiency of 1.44% using an aqueous polysulfide electrolyte with a short-circuit photocurrent density of 11.3 mA cm −2 when CdSe pebbles were annealed in a vacuum. Graphical abstract: Under AM 1.5G illumination, the CdSe photoanodes had an improved power conversion efficiency of 1.44% using an aqueous polysulfide electrolyte with a short-circuit photocurrent density of 11.3 mA cm −2 when CdSe pebbles were annealed in a vacuum.